2020
DOI: 10.3390/ijms22010369
|View full text |Cite
|
Sign up to set email alerts
|

Pigment Epithelium-Derived Factor (PEDF) Receptors Are Involved in Survival of Retinal Neurons

Abstract: The demise of retinal ganglion cells (RGCs) is characteristic of diseases of the retina such as glaucoma and diabetic or ischemic retinopathies. Pigment epithelium-derived factor (PEDF) is a multifunctional secreted protein that mediates neuroprotection and inhibition of angiogenesis in the retina. We have studied expression and regulation of two of several receptors for PEDF, patatin-like phospholipase 2 gene product/PEDF-R and laminin receptor (LR), in serum-starved RGC under normoxia and hypoxia and investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 45 publications
1
13
0
Order By: Relevance
“…We also investigated how deletion of the PEDF gene impacts expression of five putative PEDF-Rs, namely ATGL, LRP6, PLXDC1, PLXDC2, and LR, 18 , 19 , 22 , 23 which are important to the neurotrophic or antiangiogenic functions of PEDF. Our results showed that all five PEDF-R were expressed and transcribed at varying levels in the TG, LG, MG, and cornea.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We also investigated how deletion of the PEDF gene impacts expression of five putative PEDF-Rs, namely ATGL, LRP6, PLXDC1, PLXDC2, and LR, 18 , 19 , 22 , 23 which are important to the neurotrophic or antiangiogenic functions of PEDF. Our results showed that all five PEDF-R were expressed and transcribed at varying levels in the TG, LG, MG, and cornea.…”
Section: Resultsmentioning
confidence: 99%
“…The protein exerts its biological function by binding to one of several putative receptors. Adipose triglyceride lipase (ATGL), 19 low-density lipoprotein receptor–related protein 6 (LRP6) also known as Wnt coreceptor, 20 the plexin domain containing 1 (PLXDC1) and 2 (PLXDC2), 21 and the laminin receptor (LR) 22 , 23 have all been identified as putative receptors through which PEDF transduces its signals. There is growing evidence for PEDF as a therapeutic agent in various ophthalmic diseases including AMD, 24 diabetic retinopathy, 14 glaucoma, 25 and diabetic keratopathy, 26 mainly through its neurotrophic 44 amino acid domain (44-mer) 27 and antiangiogenic 34-mer.…”
mentioning
confidence: 99%
“…Therefore, we consider that it is necessary to further explore the mechanism of the role of serine protease system in SCI. Furthermore, various anticoagulants (dabigatran, rivaroxaban, warfarin) are used for anticoagulation in the treatment of SCI, and some serine protease inhibitors (ulinastatin, neuroserpin, pigment epithelium-derived factor) have been shown to be neuroprotective [ 42 44 ], our study may provide guidance of administration time window selection for their future clinical application in SCI treatment.…”
Section: Discussionmentioning
confidence: 99%
“…What may cause the hyperresponsiveness of platelets? A possible cause of platelet hyperreactivity in patients with glaucoma may involve the pigment epithelium-derived factor (PEDF), which is a multifunctional secreted protein that mediates neuroprotection and inhibition of angiogenesis in the retina ( 21 ). PEDF is significantly reduced in glaucomatous eyes ( 22 ), which may lead to increased platelet aggregability and the establishment of a thrombogenic state.…”
Section: Discussionmentioning
confidence: 99%